2017
DOI: 10.1080/00273171.2017.1370364
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Mixed Markov Models for Intensive Longitudinal Data

Abstract: Markov modeling presents an attractive analytical framework for researchers who are interested in state-switching processes occurring within a person, dyad, family, group, or other system over time. Markov modeling is flexible and can be used with various types of data to study observed or latent state-switching processes, and can include subject-specific random effects to account for heterogeneity. We focus on the application of mixed Markov models to intensive longitudinal data sets in psychology, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Applications of regime-switching models to momentary experience data pose particular data analytic challenges because time intervals between EMA measurements have varying lengths. We took the approach of discretizing and imputing gaps in the time series, but we expect that future statistical advances will contribute to improved implementation of regime-switching models with EMA data [3,13,25]. Future research may also wish to examine whether regime-switching measures derived from EMA ratings contribute to the prediction of outcomes beyond end of day ratings of least, worst, and average pain.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of regime-switching models to momentary experience data pose particular data analytic challenges because time intervals between EMA measurements have varying lengths. We took the approach of discretizing and imputing gaps in the time series, but we expect that future statistical advances will contribute to improved implementation of regime-switching models with EMA data [3,13,25]. Future research may also wish to examine whether regime-switching measures derived from EMA ratings contribute to the prediction of outcomes beyond end of day ratings of least, worst, and average pain.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the VAR(1) model, because it has become an extremely popular model for intensive longitudinal data (see Appendix E). HMMs are also a popular class of time series models in psychological research (Asparouhov et al, 2017;de Haan-Rietdijk et al, 2017;Neale et al, 2016;Visser, 2011) and the TVAR(1) model is an interesting extension of the VAR(1) model (De Haan-Rietdijk et al, 2016;Hamaker et al, 2009Hamaker et al, , 2010Hamaker et al, , 2016, which allows us to discuss how theoretical input can mitigate the problem of misspecification. Each of these models is misspecified, which means that the true system is not a special case of the model at hand.…”
Section: The Problem Of Misspecificationmentioning
confidence: 99%
“…In particular, we compared the estimates for the two models to determine which one provided the most useful and realistic substantive description of the data. We concluded that the three-state model accounted for a more sensible and complete description of set-shifting performances (see [35] for a similar approach). The reader is referred to the Supplementary Material for a more detailed comparison of models’ estimates.…”
Section: Materials and Methodsmentioning
confidence: 99%